Are peritoneal protein losses related to peritonitis risk in patients on peritoneal dialysis? - Rodrigues,Sara Daniela (2018)
Background: Peritoneal protein losses (PPL) are an inevitable process in peritoneal dialysis (PD). Few studies have supported a positive correlation between PPL and infections or general morbidity and mortality. The aim of this study was to investigate whether PPL was a risk factor of peritonitis. Methods: We retrospectively studied all incident PD patients in a PD single unit during the previous 10 years. We recorded baseline PPL (bPPL) and relevant analytic and clinical data. Patients were distributed into one of 2 bPPL groups (group 1: ≤5.89g/day and group 2: >5.89g/day) to compare their peritonitis risk. Results: 104 Patients were included, with a median follow-up of 29 months. Higher bPPL patients were more likely to have peritonitis (group 1: 43%, group 2: 72%, p<0.01). After adjustment for covariates, bPPL remained an independent predictor of peritonitis (p=0.01). The time to first peritonitis was shorter in the group with higher bPPL (p=0.01) although after adjustment for other covariates no significant associations were found. In the Poisson regression, more elevated bPPL were associated with higher peritonitis rates after adjustment for other independent variables (p=0.02). Conclusion: In this retrospective study, higher bPPL were able to independently predict risk of peritonitis, reflecting its impact on the morbidity of PD patients. Patients with higher bPPL levels presented shorter peritonitis-free time to first peritonitis episode and higher probability of more peritonitis episodes over time.